miR-129-5p Plays an Anticancer Role in Colon Cancer by Targeting RSF1 - Hao, Junfeng; Wei, Hongxia; Qi, Yabin; Liu, Haiwang (Cellular and Molecular Biology, 2022)
This study aimed to investigate the inhibitory effect of miR-129-5p on colon cancer by targeting RSF1. For this purpose, real-time quantitative PCR was used to analyze whether the expression of miR-129-5p in colon cancer and adjacent normal tissues had an impact on the proliferation and apoptosis of cancer cells (CC). We evaluated the role of miR-129-5p by targeting RSF1 in colon cancer tissue in the experimental group. But in the control group, only miR-129-5p was considered as a protective factor. Finally, we retrospectively analyzed data of 56 cases of colon cancer patients admitted to our clinical department between January 2019 and December 2019. Twenty-eight cases were investigated through just miR-129-5p protective factors for cancer (group A). The other 28 cases were studied by miR-129-5p anti-cancer agent and a completed RSF1 carcinoma factors for cancer (group B). We evaluated the comparative analysis of the patient's age and gender, clinical indicators (including for the first time of hospitalization and postoperative hospital stay, three times of anal exhaust), and complications (including chills, vomiting, hypertension, diabetes). The results showed that miR-129-5p had a more substantial effect on the proliferation and apoptosis of CC by targeting RSF1.